Evaluation of Tribological aspects of Al-Si 12 alloy and their Metal Matrix hybrid Composites produced by Liquid-metal Forging Method - Ibrahim A. ALNASER; Mohammed YUNUS; Turki ALAMRO; Rami ALFATTANI (Journal of Materials and Engineering Structures, 2022)
Particulate Aluminium Metal Matrix Composites (Al-MMC) have emerged as advanced engineering materials in view of their improved properties. Ceramic reinforced Al-MMC were more suitable because of being economical and exhibiting isotropic properties. Al-MMCs manufacturing methods are expensive, demand skilled and complex operations and vortex liquid metallurgy results into higher porosity. The liquid-metal forging/squeezed casting of stirred molten slurry can eliminate porosity as molten metal is pressurized during solidification forming near net shapes. During many instances, influence of process parameter (PP)s on mechanical part properties is being studied. In the present study, composites were produced using Al-Si12 alloy as base material, aluminium oxide and silicon carbide particles as reinforcements by varying the PPs. Tribological tests were conducted under dry sliding condition at room temperature showed hard reinforcements in Al alloy reduced the wear rate (WR) and increased the coefficient of friction (f) for all PPs. For PPs, increasing the squeeze pressure and decreasing the pouring and die preheating temperature resulted in a reduction of WR and f with an increase in normal load and sliding velocity. Initially f falls and then raised with an increase in normal load, but only raised with growing sliding velocity compared to Aluminium base material.